The Effect of Understanding Continuous Improvement and Training on Employee Performance in a Garment Company - Sunardi, Sakopa Maida (Universitas Nusa Putra, 2025)
Continuous Improvement and training are important aspects in improving employee performance and maintaining company productivity in garment production, including at PT Garmen XYZ in Sukabumi. This study aims to determine the effect of understanding Continuous Improvement and Training on Employee Performance at PT Garmen XYZ. A quantitative method was used with a questionnaire as the instrument. A sample of 67 employees in the PT Garmen XYZ production line was selected using Cluster Proportional Random Sampling. Statistical analysis included multiple linear regression, t-test, and F-test. The results showed that Continuous Improvement had a positive effect on employee performance at PT Garmen XYZ with a coefficient of determination of 0.229, but this effect was not significant (t = 1.60; Sig = 0.114). Training showed a positive effect with a regression coefficient of 0.250, but it was not statistically significant (t = 1.432; Sig = 0.157). Simultaneously, both had a positive and significant effect on employee performance (F = 13.559; Sig = 0.000). The highest indicator in Continuous Improvement was Seisou (Shine), while the lowest score was in Seiton (Set in Order). In training, the Goal indicator obtained the highest score and the Process indicator became the lowest. These results emphasize the importance of implementing and combining Continuous Improvement and Training in order to create a more efficient and productive work environment.